Polysaccharide stabilized nanoparticles for deacidification and strengthening of paper. Issue 42 (7th April 2015) - Amornkitbamrung, Lunjakorn; Mohan, Tamilselvan; Hribernik, Silvo; Reichel, Victoria; Faivre, Damien; Gregorova, Adriana; Engel, Patricia; Kargl, Rupert; Ribitsch, Volker
Abstract : This paper reports an investigation on the use of a highly stable colloidal organic dispersion consisting of a polysaccharides and alkaline nanoparticles for the simultaneous deacidification and strengthening of historical wood pulp papers. Abstract : This paper reports an investigation on the use of a highly stable colloidal organic dispersion consisting of a polysaccharide derivative and alkaline nanoparticles for the simultaneous deacidification and strengthening of aged historical wood pulp (HWP) and new paper. Colloidal dispersions of Mg(OH)2 nanoparticles (size ca. 150 nm) stabilized by trimethylsilyl cellulose (TMSC) in hexamethyldisiloxane (HMDSO) are employed for paper treatments. The influence of the polymer shell on the morphology of the particles and the stability of the dispersions, and polymer–particles interactions are examined. A correlation between the polymer concentration and stability of the nanoparticles is established. The influence of the particle–polymer coatings on the optical appearance, the pH, the alkaline reserve and the strength of the paper is investigated by pH-measurements of cold-extracts, back-titrations, artificial aging and mechanical testing. Infrared spectroscopy confirmed the irreversible deposition of nanoparticles and TMSC on the paper. The surfaces are evenly coated as confirmed by electron microscopy and contact angle measurements, and the coating does not change the optical appearance of the paper. Results from pH measurements and back-titrations have proven neutralization of acids and an alkaline reserve of 60 meq [OH − ]/100 g of paper before aging and 41 meq [OH − ]/100 g of paper after aging. Upon aging TMSC is hydrolyzed into cellulose and the coated paper exhibits a 20% higher tensile strength than uncoated paper.